منهج سعيد النورسي في التعامل مع الأحاديث المتشابهة في "رسائل النور" : دراسة تحليلية - Nur Aina Mardhiah binti Che Rahim (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
This study examines Said Nursi's methodology in dealing with the al-Hadith al-Mutasyabihat in his work of “Rasail al-Nur”. This study explored how he approached the meaning of al-Hadith al-Mutasyabihat, whereby the researcher analyzes the rank of the Hadith by extracting them from the books of Hadith and mentioning their status. Then the researcher used the review and reading to discuss opinions of scholars (muhaddithin) and mentioned the results of each of them. The researcher relied on the inductive method, through readings of “Rasail Al-Nur”, the “Nine Canonical Books of Hadith” (Al-Kutub Al-Tis'ah) with Mustadrak Al-Hakim, together with various books of commentaries with the identification of al-Hadith al-Mutasyabihat, as well as books of languages (lughat) and dictionaries (ma'ajim). To complete the research, the analytical method was used by way of reading texts related to the subject and analyzing them to discover the features of Said Nursi's methodology in dealing with al-Hadith al-Mutasyabihat. The study has found that Said Nursi was very concerned with protecting the texts of the Prophetic Hadith as shown in his efforts to reform his dealing with al-Hadith al-Mutasyabihat. It is believed to contain invalid meanings with regard to the interpretation of those Hadith in view of Islamic Law and the clear mind as stated in the twelve general principles and rules which guide the understanding of the Prophetic Hadith. The study has also proven that his approach in dealing with al-Hadith al-Mutasyabihat was based on many different sources of books of Hadith, and that most of his independent judgements (ijtihad) agreed with the scholars. This study concludes with several beneficial recommendations; the first of which is to recommend that researchers in the field of hadith study the Hadith mentioned in “Rasail al-Nur” which are not mentioned in the “Six Canonical Books of Hadith” together with their ranks. Second, the researcher proposes to study the rules based on the methodology of the scholars at the time when Said Nursi took great interest in the Prophetic Hadith as stated in the twelve general principles and rules. In addition, the researcher proposes to study Said Nursi's methodology in criticizing problematic Hadith without bias or tendency towards a particular stance, but to review the scholars' words purely for the Hadith.